A synopsis of Emilia (Senecioneae, Asteraceae) in southern Africa - Cron, Glynis Valerie (Phytotaxa, 2014)
Six species of the mainly tropical genus Emilia (Asteraceae, Senecioneae) occur in southern Africa. These species are generally not well known as no revision of the genus on a global scale has as yet been undertaken and previous work has focussed on eastern, central and northern Africa. A new combination, Emilia schinzii (syn. E. ambifaria), is proposed here because of priority. Detailed descriptions, distribution maps and a key to the southern African species are presented in this synopsis. Lectotypifications for E. limosa, E. marlothiana, E. schinzii and E. transvaalensis are provided. Included is information relevant to conservation of the species in the form of red data assessments and notes.